Gambaran Risiko Penyakit Hipertensi pada Mahasiswa - Uswatun Nisa (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Hypertension is the condition of blood pressure more than 120/80 mmHg in rest position. The purpose of this study illustrate the risk of hypertension at student Scienntific 3 Nursing Program Blitar Method: The research design was description design. The population are all students who study at Scienntific 3 Polytechnic Campus Health Ministry of Health Malang by 294 students, the total of samples this study were 224 student and using quota sampling technique. The data was collected by Risk Score for Predicting Near-Term Incidence of Hipertension. Result: The result showed that risk 1 years ago 100% have low risk, risk 2 years ago 99,1% have low risk, 9% have midle risk, and risk 4 years ago 93,8% have low risk, 5,4% have midle risk, 9% have high risk. Discussion: Recomendation from this study are expected to be used as as consideration to create a new program in of healthy prevent hypertension on students.